Penetapan Portofolio Saham Optimal menggunakan Pendekatan Model Indeks Tunggal sebagai Dasar Keputusan Investasi (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to construct an optimal stock portfolio using the Single Index Model approach on stocks listed in the IDX30 index during the 2020 to 2024 period. The research employs a descriptive method with a quantitative approach, using secondary data including stock closing prices, the Jakarta Composite Index (JCI), and the Bank Indonesia interest rate (BI Rate), all sourced from official websites. Data analysis techniques follow the Single Index Model procedures, involving calculations of alpha, beta, residual risk, and excess return to beta ratio to determine which stocks qualify for inclusion in the optimal portfolio. The results show that seven stocks—AKRA, ANTM, UNTR, BRPT, ISAT, INCO, and PTBA—qualify for the optimal portfolio as they exhibit positive alpha and beta values and contribution (Ci) scores higher than the cut-off point (C*) of 14.6593. The highest portfolio weight is allocated to AKRA at 34.86 percent. The constructed portfolio yields an expected return of 2.99 percent, a variance of 0.0659, and a portfolio angle of 0.3940, indicating that the portfolio is efficient. This study offers practical implications for investors in making quantitatively-based investment decisions and provides recommendations for future studies to expand the observation period and explore alternative portfolio models.